2000
DOI: 10.1007/s002470050761
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid follicular carcinoma: a case report

Abstract: We present an 8-year-old boy with thyroid follicular carcinoma. Differentiated thyroid follicular carcinoma is very uncommon in childhood and is not usually suspected as the explanation of a thyroid nodule during infancy. The purpose of our paper is to demonstrate the imaging findings in a child and to emphasise the importance of including this tumour in the differential diagnosis of thyroid nodules in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Although no systemic information about childhood MIFC was reported, studies about adult MIFC showed that MIFC patients had younger mean age, smaller size of the primary tumour and lower incidence of extra-thyroidal extension when compared with the whole FC group. 4,19,22 Similar with most childhood and adulthood FC cases, 4,14,15 two paediatric cases in our study presented a neck palpable mass. We did not find palpable swollen lymph nodes, hoarseness or other symptoms caused by distance metastases in these two cases, although some studies showed that childhood FC also can present these symptoms or signs.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Although no systemic information about childhood MIFC was reported, studies about adult MIFC showed that MIFC patients had younger mean age, smaller size of the primary tumour and lower incidence of extra-thyroidal extension when compared with the whole FC group. 4,19,22 Similar with most childhood and adulthood FC cases, 4,14,15 two paediatric cases in our study presented a neck palpable mass. We did not find palpable swollen lymph nodes, hoarseness or other symptoms caused by distance metastases in these two cases, although some studies showed that childhood FC also can present these symptoms or signs.…”
Section: Discussionsupporting
confidence: 81%
“…Only two reliable histological criteria, capsular and vascular invasion, are known to detect malignancy before local invasion or metastases. Thyroid nodule is common in children, and it is difficult to distinguish whether the mass is malignant or benign 15,29 . Some studies suggested that the mass should be screened while the size is over 1.5 cm 30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations